J. K. Lasser's Your Income Tax 2011 - Eiss, Elliot (Wiley ; John Wiley & Sons, 2011)
America's number one tax guide for professionals J.K. Lasser's Your Income Tax, Professional Edition 2011 is an essential guide for tax professionals. Filled with easy-to-use tax planning tips and strategies, this comprehensive guide arms you with the information needed to maximize your clients' tax savings